The Effectiveness of Maternity Nursing Digital Educationon Postpartum Maternal Health - I Gusti Ayu Ratih; Agustini (Jurnal Ragam Pengabdian, 2026)
Thisstudyaimstoanalyzetheeffectivenessofdigitaleducationinmaternity nursing on improving postpartum maternal health through a qualitative approach using a literature review (library research) method. Digital education has become an important innovation in maternity nursing services,particularlyduringthepostpartumperiod,whichisacriticalphase for mothers’ physical and psychological health. The research method was conducted by examining various scientific sources, including national and internationaljournalarticles,academicbooks,andrelevantresearchreports published within the last ten years. The analysis process involved identification, classification, and synthesis of findings to obtain a comprehensive understanding of the roles, benefits, and challenges in implementing digital education for postpartum mothers. the results of the review indicate that digital maternity nursing education is effective in improving mothers’ knowledge regarding self-care, lactation management, early detection of complications, and postpartum mental health. Furthermore, the use of digital media such as health applications, educational videos, and telehealth platforms has been shown to enhance access to information, increase maternal engagement in decision-making, andimproveadherencetocarerecommendations.However,itseffectiveness is influenced by factors such as digital literacy, family support, and the availabilityoftechnologicalinfrastructure.inconclusion,digitaleducationin maternity nursing has significant potential to holistically support postpartum maternal health. Therefore, adaptive and needs-based implementation strategies are required to optimize its benefits in nursing practice